2016
DOI: 10.1515/ohs-2016-0019
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Cladophora and coexisting filamentous algae in relation to environmental factors in freshwater ecosystems in Poland

Abstract: Potential factors affecting the occurrence of filamentous algae include the morphometry of water bodies, the type of substrate and physicochemical conditions of the habitat. This study attempts to describe the individual filamentous algae species recorded in Poland, taking into account the trophic and ecological characteristics based on our own research and available literature data. Filamentous algae attached to the substrate as well as those forming free-floating patches (loose or dense mats) and crusts occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…The wide ecological range and fast growth of C. glomerata is a strategy which allows it to establish dominance over other macroalgae in water ecosystems [13]. This fact, confirmed in previous studies, has shown that the species belonging to the genus Cladophora (C. glomerata, C. rivularis, C. fracta) well tolerates a wide range of habitat requirements [12,14]. Additionally, mat formation, morphological variability, and chemical defense strategies used by FGA are the components of its stress avoidance mechanisms.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…The wide ecological range and fast growth of C. glomerata is a strategy which allows it to establish dominance over other macroalgae in water ecosystems [13]. This fact, confirmed in previous studies, has shown that the species belonging to the genus Cladophora (C. glomerata, C. rivularis, C. fracta) well tolerates a wide range of habitat requirements [12,14]. Additionally, mat formation, morphological variability, and chemical defense strategies used by FGA are the components of its stress avoidance mechanisms.…”
Section: Introductionsupporting
confidence: 53%
“…We have shown for the first time the evidence of morphological changes at the cellular level in the filaments of C. glomerata in response to a biotic factor which is the appearance of exudates as a result of thalli accumulation. The effect of abiotic factors on morphological changes has been partly described by Whitton [16], Pikosz and Messyasz [12]. Filamentous green algae often form monospecies mats in water ecosystems.…”
Section: Disscusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly investigated macroscopic green algae in Polish freshwater ecosystems is Cladophora glomerata (L.) Kütz. (Pikosz & Messyasz ) but other taxa including Ulva (Messyasz & Rybak ) and Oedogonium (Szymańska et al ) have also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Polish reservoirs of algal biomass lie in the lakes and rivers, not in the sea -but those are still considerable [5]. Often perceived as a nuisance or an outright danger to biodiversity (when in bloom), naturally occurring algal species like Cladophora glomerata or Ulva flexuosa find little to no use in the abovementioned sectors of industry.…”
Section: Introductionmentioning
confidence: 99%